Progress in the Synthesis of Heterocyclic Compounds Catalyzed by Lipases - Ma, Xiao-Long; Wang, Yu-Han; Shen, Jin-Hua; Hu, Yi (Pharmaceutical Fronts, 2021)
Heterocyclic compounds are representative of a larger class of organic compounds, and worthy of attention for many reasons, chief of which is the participation of heterocyclic scaffolds in the skeleton structure of many drugs. Lipases are enzymes with catalytic versatility, and play a key role in catalyzing the reaction of carbon–carbon bond formation, allowing the production of different compounds. This article reviewed the lipase-catalyzed aldol reaction, Knoevenagel reaction, Michael reaction, Mannich reaction, etc., in the synthesis of several classes of heterocyclic compounds with important physiological and pharmacological activities, and also prospected the research focus in lipase-catalyzed chemistry transformations in the future.
Keywords: lipases; synthesis; heterocyclic compounds